PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR KIMIA - St Suwaibah Hasyim (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2023)
The purpose of this study was to determine the increase in learning outcomes of elemental chemistry through the application of the STAD type cooperative learning model. The research subjects were students of class XII MIPA 1 Madrasah Aliyah Negeri Luwu in the academic year 2022/2023. Research objects are activities and learning outcomes of chemistry. Student learning activity data were collected using observation sheets while student learning outcomes were collected using learning achievement tests. The data obtained were then analyzed descriptively qualitatively. The results of the study were as follows: (1) learning chemistry using the STAD type cooperative learning model could improve learning outcomes of elemental chemistry from cycle I to cycle II and student activity in learning increased from cycle I to cycle II; (2) completeness of learning classically achieved by students in the first cycle was 76.47% with a class average score of 78.32 and in the second cycle increased to 91.18% with a class average score of 86.41. (3) the learning activeness achieved by students classically in the first cycle was 65.45%, increasing in silkus II to 81.82%. Based on the above results by paying attention to the indicators of the implementation of complete learning, it can be concluded that the objectives of this research were achieved and the formulated action hypothesis was acceptable. Keywords: learning outcomes, activities, STAD.